Pengembangan Model Mencit Alergi dengan Paparan Kronik Ovalbumin - Barlianto, Wisnu; Kusuma, Mohamad Slamet Chandra; Karyono, Setyawati; Mintaroem, Karyono (Fakultas Kedokteran Universitas Brawijaya, 2009)
ABSTRACTHistology expression in asthma show inflammatory processes and airway structural changes. Treatmentdevelopment in asthma needs appropriate animal models but most animal models use short term allergenexposure. The aim of this research was to create develop allergic mouse model with allergic inflammationand structural changes histology expression. Eight female BALB/c mice, 6-12 weeks old, 80-100 gramswere divided into two groups. The first group were exposed to a normal saline solution where the secondgroup received ovalbumin. Mice were sensitized by intraperitoneal injection of ovalbumin on day 0 and 14and challenged by nebulization of 1% ovalbumin three times weekly for 6 weeks. Twenty four hours afterfinal exposure, the mice were sacrificed by lethal cardiac puncture. The level of total IgE in serum weremeasured by ELISA and IL-4 receptor expression were examinated by immunohistochemistry.Morphometric analysis was performed to count inflammatory cells, eosinophil, goblet cells, epithel andsmooth muscle thickness. Differences between the control and exposed mice were analyzed by Mann-Whitney test. There were a significant differences in total IgE serum and expression IL-4 receptor betweenthe two groups (P < 0,05). The morphometric analyzing also demonstrated significant differences betweenthese two groups (P < 0,05). Chronic ovalbumin exposure through inhalation produced allergicinflammation and airway structural changes.Keywords: allergic inflammation, mouse models, chronic exposure, ovalbumin